Neoadjuvant chemotherapy for carcinoma of the oesophagus and oesophago-gastric junction: a six-year experience - Halliday, Brian P (BioMed Central, 2007)
BACKGROUND: Oesophageal cancer is a major clinical problem with a generally poor prognosis. As a result there has been interest in combining surgery with neoadjuvant chemotherapy to try and improve outcomes, although the current evidence for benefit is inconsistent. We aimed to compare, in a non-randomised study, the post-operative complication rate and short and long-term survival of patients who underwent surgical resection for carcinoma of the oesophagus and types I and II carcinoma of the oesophago-gastric junction with or without neo-adjuvant chemotherapy. METHODS: Details of all resections for oesophageal/junctional (types I and II) adenocarcinoma or squamous cell carcinoma between April 2000 and July 2006 were collected prospectively. Data from patients with T3 and/or N1 disease who underwent either neoadjuvant chemotherapy (NAC) or not (non-NAC) were compared. Data were analysed using Kaplan-Meier plots, Mann-Whitney U-test, Cox Regression modelling, and Chi-squared test with Yates' correction where sample sizes <10. RESULTS: 167 patients were included (89 NAC and 78 non-NAC). The in-hospital post-operative mortality rate of the NAC group (n = 2 deaths; 2.2%) was significantly lower (p = 0.045) than the non-NAC group (n = 6 deaths; 7.7%). Most deaths were due to cardio-respiratory complications; however, there was no significant difference in rates of chest infections, anastomotic leaks, wound infections, re-operations, readmission to ITU or overall complications between the two groups. Although both the two-year survival rate (60.7%) and long-term survival of NAC patients (median survival = 793 days; 95% CI = 390–1196) was greater than non-NAC patients (two-year survival rate = 48.7%; median survival = 554 days; 95% CI = 246–862 respectively), these differences were not statistically significant. CONCLUSION: This non-randomised study demonstrated that NAC was associated with a significant reduction in post-operative inpatient mortality rate. Whether this can be explained by a decreased co-morbidity in NAC patients or a protective phenomenon associated with NAC remains unclear. This study also demonstrated a greater two-year survival rate and overall median survival time following NAC but this was not statistically significant.